AN ECONOMIC ANALYSIS OF DETERMINANTS OF WHEAT PRODUCTION SUPPORT IN IRAQ FOR THE PERIOD 1990-2016 - &Al-Hiyali, Noori (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2019)
This research was aimed to identify the most important factors affecting the production of wheat crop in Iraq for the period 1990-2016. The ARDL model was used to interpret the relationship between the dependent variable and the independent variables in the search. The research concluded that the continuous increases in the population would lead to increases in support to the wheat crop due to the increase in consumer demand for this crop, which prompts the state to try to encourage producers to achieve increases in production. The research also found that increases in inflation led to higher levels of support because rising inflation rates unfairly distribute income among individuals, therefore the government is moving to increase the volume of support to address this. The research recommended the need to determine the purchase prices in a way that guarantees a fair price for farmers to cover their costs and ensure a sufficient profit to stimulate production. All this will work positively to reduce imports and achieve self-sufficiency.